2018
DOI: 10.29315/gm.v5i1.135
|View full text |Cite
|
Sign up to set email alerts
|

Psicopatologia na Infância: Levantamento Epidemiológico

Abstract: RESUMOINTRODUÇÃO: As perturbações psiquiátricas da infância podem persistir durante a adolescência e vida adulta, vindo a ter um impacto negativo e que pode afetar o desenvolvimento e a autonomia do futuro adulto. O presente estudo epidemiológico surgiu da necessidade de conhecer a probabilidade de psicopatologia na infância, na população do primeiro ciclo do concelho de Vila Franca de Xira. Um dos objetivos é permitir, de forma sustentada, aferir as necessidades reais, do ponto de vista da Saúde Mental, da po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In this sense, we sought to analyze the socioemotional development of children of imprisoned men and its relationship with their parenting practices. The results indicated that the prevalence of clinically relevant socioemotional difficulties was similar to that commonly found in studies with general population samples, about 11% (Fleitlich-Bilyk & Goodman, 2004;Moura et al, 2018;Polanczyk et al, 2015). Furthermore, parenting practices of affection, education, and socialization were directly associated with socioemotional development, while those of discipline were inversely correlated.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this sense, we sought to analyze the socioemotional development of children of imprisoned men and its relationship with their parenting practices. The results indicated that the prevalence of clinically relevant socioemotional difficulties was similar to that commonly found in studies with general population samples, about 11% (Fleitlich-Bilyk & Goodman, 2004;Moura et al, 2018;Polanczyk et al, 2015). Furthermore, parenting practices of affection, education, and socialization were directly associated with socioemotional development, while those of discipline were inversely correlated.…”
Section: Discussionsupporting
confidence: 74%
“…Another important result was that there was no significant difference between genders for the SDQ. There is no consensus in the literature about this topic, while some studies found no differences (e.g., Moura et al, 2018;Stivanin et al, 2008); others reported, for example, higher mean scores for females in emotional symptoms (Saud & Tonelotto, 2005) and higher mean scores for males in hyperactivity and females in pro-social behaviors (Cury & Golfeto, 2003). It is relevant to point out that children are still socialized differently according to gender, which can impact on distinct emotional and behavioral expressions (Pirlott & Schmitt, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation